New WHO recommendations on intraoperative and postoperative measures for surgical site infection prevention: an evidence-based global perspective. Issue 12 (December 2016) - Allegranzi, Benedetta; Zayed, Bassim; Bischoff, Peter; Kubilay, N Zeynep; de Jonge, Stijn; de Vries, Fleur; Gomes, Stacey M; Gans, Sarah; Wallert, Elon D; Wu, Xiuwen; Abbas, Mohamed; Boermeester, Marja A; et al.
Summary: Surgical site infections (SSIs) are the most common health-care-associated infections in developing countries, but they also represent a substantial epidemiological burden in high-income countries. The prevention of these infections is complex and requires the integration of a range of preventive measures before, during, and after surgery. No international guidelines are available and inconsistencies in the interpretation of evidence and recommendations in national guidelines have been identified. Considering the prevention of SSIs as a priority for patient safety, WHO has developed evidence-based and expert consensus-based recommendations on the basis of an extensive list of preventive measures. We present in this Review 16 recommendations specific to the intraoperative and postoperative periods. The WHO recommendations were developed with a global perspective and they take into account the balance between benefits and harms, the evidence quality level, cost and resource use implications, and patient values and preferences.